(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
Employees are the biggest resource for the organization. All the strategies of the organization are implemented with the help of human resources. Thus it becomes important to ensure that human resources are satisfied and take active participation regarding matters related to their job. Nowadays employees want some autonomy related to their work. If the employee feels powerless they may experience learned helplessness. Learned Helplessness at working environment can leads to disengagement, role stress, and agitated employee. This study aims at analyzing the relationship between learned helplessness and job attitudes. Results indicate that there exists a negative relationship between learned helplessness and job satisfaction and job involvement. Further, gender has a moderating effect on the impact of learned helplessness on job involvement.